Una víctima del encuentro emergente entre mundos - Minna Opas; Yulissa Trigoso Zorrilla (Society for the Anthropology of Lowland South America, 2022)
In February 2018 Víctor Zorrilla, an elderly Yine man living in southeastern Peru, was killed by the Mashco Piro while hunting. Zorrilla had over the decades met with the mashco piro who he considered as kin, nomolene, various times, but that did not prevent him from becoming a victim of an emerging encounter between worlds. Through a personal account of his encounters with the Mashco Piro people in the 1980s, this article raises and explores several focal questions related to voluntary isolation. How can knowledge concerning the isolated people’s be acquired in an etically sustainable manner? What are the implications of the notions used in speaking about isolation, ’contact’ in particular? How can protection of voluntarily isolated people or those in initial contact be carried out without compromising the safety of the neighboring peoples?